Impact of hygienic milk production training on knowledge, attitudes and practices of women farmers in the central highlands of Ethiopia - Keba, Abdi; Tola, A.; Kaylegian, K.E.; Kebede, M.; Zewdu, A. (Frontiers Media, 2025)
Introduction: Food safety remains a challenge in developing nations, including Ethiopia, where dairy products are known to be contaminated with foodborne pathogens. Limited food safety interventions studies for improving food safety along the food supply chain have been conducted. The objective of this intervention study was to improve the knowledge, attitudes, and practices (KAPs) of women dairy farmers in the central highlands of Ethiopia by developing and delivering training customized to their education level.